The Construction of Indigenous Language Rights in Peru: A Language Regime Approach. Issue 2 (August 2019) - Rousseau, Stéphanie; Dargent, Eduardo
From the 1990s onwards, many Latin American states have adopted constitutional reforms that recognise indigenous peoples' rights. In this article, we address a much less studied aspect, the emergence of new language rights. Based on field research and process tracing, we study the case of Peru where indigenous language rights were created in the absence of ethnic parties and with a relatively weak indigenous movement. We argue that the country moved slowly away from a monolingual language regime towards the recognition of indigenous languages as official languages and the creation of language rights. We identify key moments of state transformation in the 1970s, the 1990s, and the 2000s as linked to successive building blocks in the creation of a multi-lingual language regime. In particular, the decentralisation reforms of the 2000s created new opportunities for subnational actors to further develop these rights in different regions of the country. We exemplify these dynamics by looking into the adoption of language rights in the regions of Cuzco and Ayacucho.